Infusion of the Critical Thinking in Chemistry through Selected Teaching Strategies - Eleanor Reyes (Philippine Association of Institutions for Research, Inc., 2017)
Critical thinking is one of the 21st Century skills involved in education and is required of students nowadays. The study investigated the critical thinking skills of Junior high school students from three selected public schools in Region 3, Luzon, Philippines.  Infusion of the critical thinking in Chemistry through selected teaching strategies of inquiry-based, problem solving, collaborative, and lecture methods. CEU-Lopez Critical Thinking Skills Test (2012) with a reliability test value of 0.87 was used to measure the students' critical thinking skill levels. Triangulation of inquiry-based teaching, problem solving, and collaborative teaching methods was used as an intervention to determine the enhancement of the respondents' critical thinking skills and academic performance. Gathered data were processed statistically through descriptive and inferential tests.  Results revealed that there is a significant difference in the critical thinking skill levels of Junior high school students in Chemistry. The critical thinking skill levels of the student respondents were highly comparable with respect on their academic performance in Chemistry.  The students demonstrated good knowledge, attitude and performance in Chemistry after the infusion of the critical thinking approach in the intervention. The different teaching strategies utilized in the research were applicable in the enhancement of the critical thinking skills of the Junior high school students in Chemistry.